Transition to parenthood and mental health at 30 years: a prospective comparison of mothers and fathers in a large Brazilian birth cohort - Pearson, R; Culpin, I; Loret De Mola, C; Quevedo, L; Murray, J; Matijasevich, A; Tiling, K; Barros, F; Stein, A; Horta, B (Springer, 2018)
Purpose: Parenthood represents a major biological, social and environmental life change. Mental health disorders are common in parents and impact both the parent and their offspring. However, the relationship between parenthood and mental health, and the direction of these effects are poorly understood. Method: Longitudinal data from the Pelotas 1982 birth cohort, Southern Brazil, on >3000 individuals was used to investigate the association between number of children by age 30 years and mental health disorders using DSM-IV diagnoses at age 30 years, suicidal risk and the change in symptoms using repeated measures (using the SRQ-20) from age 19 to 30 years. Results: Mothers, but not fathers, with higher number of children by age 30 years were at a substantially increased risk of a wide range of mental health disorders compared to women with no children (adjusted odds ratio (OR) for suicidal plans: 5.99, 95%CI 2.51 to 14.30, p<0.001). There was evidence that motherhood was associated with an increase in symptoms over time rather than higher symptoms at baseline. Younger age at first child was also a risk factor for mental health disorders. Conclusions: Mothers, particularly those with multiple children, are at risk of a wide range of mental health disorders. The mechanisms to explain these risks are yet to be elucidated, however, the risk of mental health disorders was not replicated in fathers, which would be expected if residual confounding explained observed associations. Thus, multiparous mothers represent a high-risk group and should be prioritised for supportive interventions.